TRAPPC11‐related muscular dystrophy with hypoglycosylation of alpha‐dystroglycan in skeletal muscle and brain. (11th November 2021) - Munot, Pinki; McCrea, Nadine; Torelli, Silvia; Manzur, Adnan; Sewry, Caroline; Chambers, Darren; Feng, Lucy; Ala, Pierpaolo; Zaharieva, Irina; Ragge, Nicola; Roper, Helen; Marton, Tamas; et al.
Abstract: Aims: TRAPPC11, a subunit of the transport protein particle (TRAPP) complex, is important for complex integrity and anterograde membrane transport from the endoplasmic reticulum (ER) to the ER–Golgi intermediate compartment. Several individuals with TRAPPC11 mutations have been reported with muscle weakness and other features including brain, liver, skeletal and eye involvement. A detailed analysis of brain and muscle pathology will further our understanding of the presentation and aetiology of TRAPPC11 disease. Methods: We describe five cases of early‐onset TRAPPC11 ‐related muscular dystrophy with a systematic review of muscle pathology in all five individuals, post‐mortem brain pathology findings in one and membrane trafficking assays in another. Results: All affected individuals presented in infancy with muscle weakness, motor delay and elevated serum creatine kinase (CK). Additional features included cataracts, liver disease, intellectual disability, cardiomyopathy, movement disorder and structural brain abnormalities. Muscle pathology in all five revealed dystrophic changes, universal hypoglycosylation of alpha‐dystroglycan and variably reduced dystrophin‐associated complex proteins. Membrane trafficking assays showed defective Golgi trafficking in one individual. Neuropathological examination of one individual revealed cerebellar atrophy, granule cell hypoplasia, Purkinje cell (PC) loss, degeneration and dendrite dystrophy, reduced alpha‐dystroglycan (IIH6) expression in PC and dentate neurones and absence of neuronal migration defects. Conclusions: This report suggests that recessive mutations in TRAPPC11 are linked to muscular dystrophies with hypoglycosylation of alpha‐dystroglycan. The structural cerebellar involvement that we document for the first time resembles the neuropathology reported in N ‐linked congenital disorders of glycosylation (CDG) such as PMM2 ‐CDG, suggesting defects in multiple glycosylation pathways in this condition. Abstract : Recessive mutations in TRAPPC11 are linked to muscular dystrophies with hypoglycosylation of alpha‐dystroglycan in skeletal muscle and brain. The structural cerebellar involvement that we document for the first time resembles the neuropathology reported in N ‐linked congenital disorders of glycosylation (CDG) such as PMM2 ‐CDG, suggesting defects in multiple glycosylation pathways in this condition.